Model Pembelajaran Student Team Achievement Division (STAD) dan Model Pembelajaran Teams Games Tournament (TGT): Dampak terhadap Hasil Belajar Fisika - Tri Ariani; Duwi Agustini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this research is to know the difference of student physics learning result by using Student Team Achievement Division (STAD) and Teams Games Tournament (TGT) learning model. The type of research used is quantitative research with experimental research method. The population in this study are all students of class VIII SMP Negeri Air Lesing. In this study the entire population used as a sample, so this research is a sample study with class VIII. 1 as experimental class I and VIII. 2 as experimental class II. The data were collected using a test technique consisting of 7 essay questions. The collected data then analyzed using ttest is tcount = 2,104 and ttable = 2,021. with criteria t count more than ttable, then H0 rejected Ha accepted. Thus the hypothesis proposed in this study accepted the truth. Based on the results of research and discussion it can be concluded that there are differences in the results of physics learning using the Student Team Achievement Division (STAD) learning model and Teams Games Tournament (TGT) learning model At SMP Negeri Air Lesing. Keywords: Learning Outcomes, STAD Teams Games Tournament (TGT)